Estimation of changes in the lake water level and area using remote sensing techniques (Case study: Lake Toba, North Sumatra). Issue 1 (August 2020) - Aziz, F; Kusratmoko, E; Mandini, M D
Abstract: The decline in water level that occurred in Lake Toba, North Sumatra lately has become an important issue for the local government and the community around the lake. Climate factors also have a great impact especially when the extreme conditions ENSO and IOD occurred. The purpose of this research is to look at the relationship between rainfall and the ENSO and IOD through the changing of Lake Toba's water surface level and area. Monitoring of the dynamics of the water surface level and area of Lake Toba can be analyzed through remote sensing by using Landsat imagery to be more effective and efficient. Then the image is processed by using the MNDWI (Modified Normalized Difference Water Index) method to separate water bodies from the land. Retrieval of Landsat imagery was taken in the range of 2008 - 2017, then selected years when the conditions of ENSO and IOD occurred. The results showed in 2008, which was the La-Nina year followed by a positive IOD, the surface area of water decreased to 4.45 km 2 from the average area, but in 2015 when the El-Nino phase followed by positive IOD the water surface area increased to 4.7 km 2 from the average area. ENSO and IOD did not have much influence on rainfall in the Lake Toba region but slightly affected the water surface level and area of Lake Toba.